أثر سعة المديونية والتدفقات النقدية الحرة في أداء الشركة دراسة تطبيقية في عينة من الشركات الصناعية المدرجة في بورصة عمان للأوراق المالية (المجلة العراقية للعلوم الاقتصادية, 2018)
The research targets to analyze the impact of debt capacity and free cash flow on the company performance, through the application to a sample consisting of (12) companies of the industrial companies listed at the Amman Stock Exchange, which accounted for almost 16% from the research population. The research was a time series represented in the five-year period from 2009 to 2013.The first independent variables is debt capacity, which represented by the asset coverage, debt coverage, and interest coverage. The second was free cash flow. The researchers depend on Lehn & Paulsen method to calculate it. And return on investment, as a proxy of firm performance, represents the dependent variable.The research used panel analysis to test the impact of the variables with multi regression at the main hypothesis (There is no significant impact of debt capacity and free cash flow on the company¢s performance, expressed as a rate of return on investment (ROI) ).The result of hypothesis test signs there is a significant impact of debt capacity and free cash flow on the company performance, and the important conclusion is that the assets coverage, debt coverage, and free cash flow are the best variables to interpret the variance of ROI. This result corresponds with knowledge framework of debt capacity and free cash flow.